2017
DOI: 10.2147/ijwh.s147006
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence on the link between depressive symptoms and bone loss in postmenopausal women

Abstract: Osteoporosis and depression are major health problems of crisis proportions in postmenopausal women. Researchers have established a relationship between bone loss and depression, although few studies have focused on postmenopausal women. The purposes of this integrative review were to synthesize and summarize the available literature on: 1) the associations between bone loss and depression in postmenopausal women; and 2) potential variables that impact the associations between bone loss and depression in postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Psychosocial: The results of a systematic review[ 32 ] showed that bone mass reduction is associated with depressive symptoms in postmenopausal women and we also achieved this result…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Psychosocial: The results of a systematic review[ 32 ] showed that bone mass reduction is associated with depressive symptoms in postmenopausal women and we also achieved this result…”
Section: Discussionsupporting
confidence: 55%
“…Adrenergic signaling suppresses osteoblast reproduction and bone growth[ 30 ] Physical: Consistent with the results of the present research, the other research showed that osteoporosis and bone fracture have a profound effect on individuals' physical activity and daily activity, and this effect occurs through a cumulative impairment cycle. This cycle involves avoiding activity, reducing muscle mass, and decreasing motor capacity, which leads to a greater risk of fracture and a greater reduction in physical activity[ 31 ] Psychosocial: The results of a systematic review[ 32 ] showed that bone mass reduction is associated with depressive symptoms in postmenopausal women and we also achieved this result Sexual: There was no statistically significant difference between the two groups regarding sexual function. It is noteworthy that in the present study, the percentage of respondents to the sexual function questions of the questionnaire was lower than other subdomains (about 90% in the normal group and about 76% in the osteoporosis group), and this may be due to separation or death of spouse, being single, unwillingness to answer such questions for cultural reasons, and lack of acceptance by participants.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the lower scores in the psychological domain, it is well known that there is an association between osteoporosis and depression [19]. Low physical functioning related to low BMD and role limitations may lead to poor emotional status [20].…”
Section: Results Discussionmentioning
confidence: 99%
“…A prospective study demonstrated that depressive symptoms are associated with greater osteoporosis burden 10 yr later (47). Furthermore, emerging evidence suggests that bone loss is related to depressive symptoms in postmenopausal women, and depressive symptoms have been suggested as a way to evaluate bone loss in postmenopausal women because osteoporosis is often silent with no symptoms until a woman experiences a fracture (48). In addition, bisphosphonates as a treatment in postmenopausal women improved depressive symptoms, as demonstrated by higher Beck depression inventory scores (49).…”
Section: Discussionmentioning
confidence: 99%